2007
DOI: 10.1021/jo0711438
|View full text |Cite
|
Sign up to set email alerts
|

Sulfur and Selenium Ylide Bond Enthalpies

Abstract: The bond dissociation enthalpies (BDEs) of sulfur and selenium ylides have been estimated by applying MP2/6-311++G(3df,2p)//MP2/6-31G(d,p), G3, and other computational methods. Computed sulfoxide bond enthalpies were compared to experimental results to ensure the reliability of the computational methods before extending to related compounds. The examined ylides include the following: sulfoxides, sulfilimines, S,C-sulfonium ylides, and selenoxides. Selenoxides have BDEs about 10 kcal/mol smaller than the corres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 23 publications
(30 citation statements)
references
References 52 publications
1
29
0
Order By: Relevance
“…Geometries were optimized with the 6-31G(d) basis set, and the respective vibrational matrices showed that each structure was a minimum. It is well known that fairly large basis sets that contain tight d polarization functions are required to get good relative energies for the oxides of sulfur [13,[40][41][42][43][44][45][46][47][48][49][50][51][52] We thus used the aug-cc-pV(T þ d)Z basis set to obtain single point energies at the so-obtained geometries (i.e., MP2/aug-cc-pV(…”
Section: Computations Regarding Furan Formationmentioning
confidence: 99%
See 1 more Smart Citation
“…Geometries were optimized with the 6-31G(d) basis set, and the respective vibrational matrices showed that each structure was a minimum. It is well known that fairly large basis sets that contain tight d polarization functions are required to get good relative energies for the oxides of sulfur [13,[40][41][42][43][44][45][46][47][48][49][50][51][52] We thus used the aug-cc-pV(T þ d)Z basis set to obtain single point energies at the so-obtained geometries (i.e., MP2/aug-cc-pV(…”
Section: Computations Regarding Furan Formationmentioning
confidence: 99%
“…[10] A much more modest degree of success was found with heavy atom substitution on the arene. [11] A much earlier hypothesis, though, was that derivatives of TO might be particularly good at deoxygenation because of their lower S-O bond dissociation enthalpies [12,13] and higher excited state energies (Table 1). (A potential flaw in this reasoning is the low triplet energy of cyclopentadiene, which might reasonably used as a first estimate for the triplet energy of TO.)…”
Section: Introductionmentioning
confidence: 99%
“…18 We believe this approach to carbene generation using one or more of the sulfonium ylides should be general for preparation of any carbene whose corresponding S,C ylide is synthetically accessible.…”
Section: Scheme 1 Photolysis Of Thiophene Ylides In Methanolmentioning
confidence: 99%
“…Such carbonization studies will be conducted in future investigations, as shown in Fig. 18a and b [96][97][98][99][100][101][102][103][104][105][106][107][108][109].…”
Section: Sulfuric Systemmentioning
confidence: 99%